Library and applications for DSP and SDR research - Pinho, David Boggon (2020)
The increasing number of connected devices and wireless protocols poses several challenges and is calling for new ways to design and implement radio systems. Technological advances in analogue-to/from-digital converters and computing power has made software-defined radio (SDR) a popular architecture. I propose an initial implementation of a library for SDR research, targeted at fellow students and digital signal processing (DSP)/SDR practitioners. The SKSDR library is developed in Python due to its well established usage in the scientific community and large body of supporting libraries and documentation. The library includes an initial implementation of several algorithms for various stages of the transmitter and receiver chains, such as modulators, matched filtering, synchronization blocks, among others. On top of the library, and as demonstration purposes, I propose two applications based on the GNU Radio SDR framework. The first application is a wideband frequency modulation (WBFM) receiver, based on an alternative algorithm, than the one already existing in the GNU Radio system. The second application is a complete PSK transceiver that works both in simulated environment and with physical hardware, real-time requirements. This is aimed at demonstrating the challenges posed by physical implementation, like real channel impairments, which sometimes are difficult to capture in simulation environment. GNU Radio will be used mostly as wrapping logic, with the main goal being full re-use of the algorithms developed for the SKSDR library. A HackRF One and RTL-SDR devices will be used as the radio front ends, for transmitter and receiver respectively.